MUTU PELAYANAN KESEHATAN TERHADAP KEHANDALAN KINERJA PEGAWAI DI PUSKESMAS PANGKALAN BALAI KABUPATEN BANYUASIN SUMATERA SELATAN (Program Studi Ilmu Kesehatan STIKES Abdi Nusa Pangkalpinang, 2022)
Work discipline is the most important operative function of Human Resources management because the better the employee discipline, the higher the workperformance that can be achieved. The purpose of this study was to determine the relationship between motivation, ability, rules, boss, length of work,remuneration and amount of remuneration with employee work discipline at Pangkal Balai Public Health Center. This study uses a quantitative method with across sectional design. The population in this study were Pangkal Balai Public Health Center employees, totaling 304 people, and the sample of this study was131 respondents. From the whole analysis process that has been carried out, it can be concluded that of the 7 independent variables, the ability variable has arelationship with work discipline. The most influential variable in multivariate analysis is ability. The ability variable is a protective variable, which means that theability can improve work discipline for Pangkalan Balai Public Health Center employees. It is recommended to be able to improve the ability of employees withinternal and external training